Repression of competition favours cooperation: experimental evidence from bacteria. - Kümmerli, R; van den Berg, P; Griffin, A; West, SA; Gardner, A (2010)
Repression of competition (RC) within social groups has been suggested as a key mechanism driving the evolution of cooperation, because it aligns the individual's proximate interest with the interest of the group. Despite its enormous potential for explaining cooperation across all levels of biological organization, ranging from fair meiosis, to policing in insect societies, to sanctions in mutualistic interactions between species, there has been no direct experimental test of whether RC favours the spread of cooperators in a well-mixed population with cheats. To address this, we carried out an experimental evolution study to test the effect of RC upon a cooperative trait - the production of iron-scavenging siderophore molecules - in the bacterium Pseudomonas aeruginosa. We found that cooperation was favoured when competition between siderophore producers and nonsiderophore-producing cheats was repressed, but not in a treatment where competition between the two strains was permitted. We further show that RC altered the cost of cooperation, but did not affect the relatedness among interacting individuals. This confirms that RC per se, as opposed to increased relatedness, has driven the observed increase in bacterial cooperation.